Anatomical Changes after Gall Bladder Surgery in Patients Come in Tertiary Care Hospital a Clinical Study for Awareness of Disease in our Population - Sehar Khowaja, Hamza Fawad, Muhammad Ali Qureshi, Muhammad Rashid, Javaid Sajjad Hashmi, Aziz Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of this study were to find out the anatomical changes among patients after gall bladder surgery and to provide awareness of disease in our population. Laparoscopic cholecystectomy is a safe and effective treatment option for gallstone disease that can be performed at tertiary care hospital with minimal morbidity. The findings of current study described that a significant(p<0.05) changes in mean standard deviation of BMI, Systolic BP, diastolic BP and serum levels of cholesterol, triglyceride, LDL and HDL after six months of cholecystectomy in both male and female were seen respectively. Because of these facts remarkable anatomical abdomen changes were identified in patients after six months of Laparoscopic and open cholecystectomy.